The Legal Position of Marriage Agreement Deeds Made by Notaries in Mixed Marriages - Rahmawati, Januar; Peni Rinda Listyawati, Peni (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Abstract. This research aims to determine and analyze the legal position of marriage agreement deeds made by notaries in mixed marriages. This legal act of mixed marriage will certainly give rise to legal consequences, namely that joint property will arise, and further problems will arise because foreign citizens cannot have property rights. For this reason, there is a law that regulates marriage agreements to provide legal protection for the parties. This research aims to determine the legal position of marriage agreement deeds made by notaries in mixed marriages and the legal consequences of marriage agreement deeds made by notaries in mixed marriages. To find out and analyze the position of marriage agreement deeds made by notaries in mixed marriages. The research method uses a sociological juridical approach, the type of research is qualitative, the data source uses primary data and secondary data, the data collection method for primary data is carried out by interviews, while secondary data uses library research, which is then analyzed descriptively qualitatively. The results of this research show that the legal position of marriage agreement deeds in mixed marriages is as a legal subject for Indonesian citizens and foreign citizens who have the same legal position, namely providing legal protection for the parties. According to the current law, the time for making a marriage agreement can be done before the marriage takes place, during the marriage or after the marriage takes place after the Constitutional Court decision number 69/PUU-Xlll/2015 and the marriage agreement executed by the parties before a notary binds the rights and obligations of the parties. The legal consequence of a marriage agreement deed made by a notary in mixed marriages is that they both have laws that bind the parties and provide legal certainty and protection for the parties. Keywords: Agreement; Marriage; Mixed.